English Author Dictionaries as Contribution to National Heritage - Karpova, Olga (Respectus Philologicus, 2021)
The paper is devoted to cultural heritage dictionaries with special reference to the oldest branch of English lexicography – author lexicography, comprising three hundred reference books of different types: concordances, glossaries, lexicons, indices, thesauri, etc. The article describes the main trends in developing author linguistic dictionaries for general and special purposes to single and complete works of G. Chaucer, W. Shakespeare, J. Milton, other famous English writers since the 16th c. up to the present days. The architecture of author encyclopedic dictionaries (guides, encyclopedias, companions) and onomasticons (dictionaries of characters and place names, who is who in … series) and their significant contribution to the English language, culture and society are discussed. The main accent is made on the digital era of English heritage lexicography, innovative features of modern printed and Internet author reference resources, aimed at certain target groups users’ needs and demands.